Integrated GEE–ERT–XRF framework for detecting in-situ rare oxide formation in tropical lowland clays - Uyu Saismana; Agus Mirwan; Sunardi; Suryajaya; Doni Rahmat Wicakso (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2026)
Understanding in-situ rare oxide formation in tropical lowlands remains challenging due to the extensive peat–clay cover and the limited surface accessibility. This study presents a reproducible integrated workflow combining cloud-based hydrographic analysis in Google Earth Engine (GEE), two-dimensional electrical resistivity tomography (ERT), and X-ray fluorescence (XRF) geochemistry to investigate rare oxide occurrence in South Kalimantan, Indonesia. MERIT Hydro data that had been processed within the GEE framework were utilized for the delineation of buried palaeochannel traces. This was followed by ERT profiling and core drilling to characterize the subsurface lithology. XRF analyses indicate Yb2O3 concentrations of 0.01–0.04 wt% and Re2O7 of 0.00–0.08 wt% within clay layers at approximately 3–4 m depth. The results of spatial correlation analysis demonstrate weak relationships between oxide distribution and palaeochannel proximity (|r| < 0.3) but strong positive relationship between resistivity and oxide concentrations (r > 0.75). The results obtained lend significant support to an in-situ formation model, primarily controlled by lithological and geochemical processes as opposed to fluvial transport. The proposed GEE–ERT–XRF workflow offers a preliminary operational framework for detecting subtle, clay-hosted rare oxide signatures in data-limited tropical lowland environments. The findings demonstrate that efficacy of subsurface resistivity as a proxy for identifying geochemical trapping horizons associated with rare oxide enrichment beneath peat–clay cover. The proposed workflow further provides a cost-effective, scalable, and reproducible approach for early-stage mineral exploration and subsurface resource screening in tropical lowland regions where conventional geological mapping is limited by poor surface exposure.